The Use of Locative Nouns Li, Shang, and Zhong as Mandarin Language Adposition - Ayu Trihardini (Lingua Cultura, 2017)
The purpose of this study was to analyze locative nouns (li, shang, and zhong) that may function as postpositions and therefore Mandarin language considered to have circumposition. The collected data were sentences taken from Chinese short stories by Lu Xun and the articles in the tabloid. Because the object of this study consisted of language in texts, hence observation and documentation method were needed. The analysis of data used distribution method with dissipative technic, substitution technic, and insert technic. Through dissipative and insert technic, the distribution of the adpositional phrase could be known. Through substitution technic, the distribution of the adpositional phrase and the use of preposition related tosemantic was conducted. The study shows, in some context of adpositional phrase, locative nouns li, shang, and zhong may function as postpositions, while the use of preposition zai, is optional, and the options provide the same meaning. Based on this result, Mandarin locative nouns should be considered as postpositions.